Risperidone Induced Extrapyramidal Side Effects: A Rare Case Report - Sakhamuri, Vikas; Valicherla, Sindhu Vaishnavi; Kona, Sai Vasudev; Besabathini, Hemanth Gopinath (Journal of Pharmacy Practice and Community Medicine)
Antipsychotics are the group of drugs chiefly used in the management of Schizophrenia. They are classified into two generations i.e., first and second generations. First-generation drugs were greatest expected to cause extrapyramidal symptoms. With the discovery of second generation antipsychotics, the lower affinity for dopamine receptors had raised expectations in the clinical community regarding the lower risk for extrapyramidal symptoms. Various antipsychotics differ in their incidence and severity of causing extrapyramidal side effects, but these second generation drugs have not encountered up to the expectation with regard to their tolerability. Extrapyramidal side effects generally consist of a group of movement disorders such as tardative dyskinesia, Pseudoparkinsonism, dystonia and akathisia. Symptoms pertained to Pseudoparkinsonsim, acute dystonia and akathisia occur early in treatment course, but tardive dyskinesia, tardive dystonia, and tardive akathisia have a late onset, occurring after years of treatment course. The acute forms of extrapyramidal side effects usually develop soon after the starting of antipsychotic use, these are dose-dependent and increases with the increase in the dose, and can be prevented after withdrawal of the insulting medication.
Keywords: Extrapyramidal side effects; Akathisia; Pseudoparkinsonism; Dystonia.